Blue economy in Southeast Asia: Oceans as the new frontier of economic development. (2nd July 2016) - Gamage, Rajni Nayanthara
ABSTRACT: While the term "blue economy" has found increasing traction with a variety of stakeholders (both state and non-state) in the recent past, a working definition of the concept at a regional or global level is yet to be arrived at. This paper begins with a brief examination of the concept of blue economy, followed by a discussion of blue economy initiatives undertaken or aspired towards at the regional level of Southeast Asia. In doing so, three fundamental propositions are made: First, the prospects for blue economy in Southeast Asia remain optimistic despite difficulties in collective action posed by the "ASEAN Way", an obstacle which appears to have been considerably overcome in the launching of the ASEAN Economic Community (AEC) in 2015. Second, Indonesia's growing economic and political profile allows it to assert the reins of regional (and even global) leadership on blue economy, without necessarily limiting itself to the Association of Southeast Asian Nations' (ASEAN) means and mechanisms. Third, while traditional security issues, both between Southeast Asian and extra-regional powers and within Southeast Asia over outstanding sovereignty and jurisdictional disputes, may impede cooperation on tackling non-traditional (maritime) security issues in the region, they may not prove as formidable an impediment against the successful realisation of blue economy initiatives.